ECU : European currency unit - Levich, Richard M., ed. (Euromoney LondonGB, 1987)
Gives overview of the Ecu's history and its uses as a financing, trading and hedging instrument. Discusses its relationship to the European Monetary System and considers the interbank, swap, bonds, syndicate credit and futures market for the Ecu. Explains the Ecu's clearing and payments system and note facilities. Examines the corporate and financial applications of the Ecu and discusses its future prospects focusing on new markets and uses. Outlines roles of the sponsors of the Ecu.